Frank H. Hitchcock papers - Hitchcock, Frank H. (Frank Harris), 1867-1935.
Correspondence, journals, clippings, photographs, and memorabilia relating largely to Hitchcock's work as U.S. postmaster general (1909-1913) and as a publisher in Arizona. Correspondents includes Albert Jeremiah Beveridge, George B. Cortelyou, and Theodore Roosevelt.
U.S. postmaster general, chairman of the Republican National Committee, and newspaper publisher
Collection material in English.
Keywords: Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; United States. -- Post Office Department; Publishers and publishing -- Arizona; Cabinet officers; Politicians; Publishers